Flagship species approach: are we heading on the right track? - Thapa, Kanchan (Conservation Science, 2014)
Aim The paper aims to evaluate the usefulness of the Flagship Species Approach (FSA) as a conservation strategy. Location The study was conducted primarily among the conservation practitioners working with the flagship species in Nepal. Material and Methods Using a structured questionnaire, a total of 89 conservationists from three different categories of conservation agencies: government, nongovernmental organizations, and intellectuals (academics and researchers), were asked about their views regarding the FSA in bringing conservation benefits and reducing the biodiversity threats. I used non-parametric tests for analyzing the data. Key findings A majority of respondents shared the view that the FSA is being used effectively in raising funds for conservation and in bringing awareness to people and enhancing conservation of other species. Level of satisfaction pertaining to FSA, however, differed among the governmental / nongovernmental organizations and the intellectual agencies. Conservation implications This study found that FSA had been instrumental in raising the funds for biodiversity conservation and keeping the science in the forerunner. DOI: http://dx.doi.org/10.3126/cs.v1i1.9585 Conservation Science 2013 1(1), 47-52